Primary hepatic extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue - Choi, Soyeon (J Pathol Transl Med, 2020)
Extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue (MALT lymphoma), is one of the specific type of low-grade B-cell lymphoma not infrequently found worldwide. It typically involves mucosal sites such as stomach and conjunctiva; however, primary hepatic MALT lymphoma has been extremely rarely reported. We describe a case of hepatic MALT lymphoma in a 70-year-old male patient who underwent left hepatectomy due to the incidentally detected liver masses at a medical checkup. The resected specimen revealed multinodular masses consisting of small-to-intermediate-sized lymphoid cells with serpentine pattern and focal lymphoepithelial lesions. The tumor cells were diffusely positive for CD20 and Bcl-2 but negative for CD3, CD10, CD5, CD23, CD43, and cyclinD1. The Ki-67 labeling index was 10% and immunoglobulin heavy chain gene rearrangement study confirmed monoclonal proliferation. In this paper, we discuss several unique clinicopathologic characteristics which will be helpful to the differential diagnosis of hepatic MALT lymphoma.